Evaluating the Prognostic Role of Pan-Immune-Inflammation Value in Patients with Advanced Non-Small Cell Lung Cancer Treated with Nivolumab - Guliyev, Murad; Alan, Özkan; Fidan, Mehmet Cem; Abbasov, Hamza; Cebeci, Selin; Aliyev, Vali; Çerme, Emir; Birsin, Zeliha; Günaltılı, Murat; Demirci, Nebi Serkan (Cerrahpaşa Medical Journal, 2025)
Objective: Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related death. Panimmune-inflammation value (PIV), a novel biomarker that reflects systemic inflammation and immune status, has been evaluated for prognostic efficacy in various cancer types. This study aimed to investigate the efficacy of PIV on survival outcomes in patients diagnosed with advanced NSCLC who were treated with nivolumab. Methods: The single-center, retrospective, and observational study included patients with metastatic NSCLC who received nivolumab treatment. The receiver operating characteristic (ROC) curve analysis was performed to find the optimal PIV cutoff value for predicting outcomes, and patients were divided into 2 groups: low-PIV and high-PIV. Results: The median age was 63 years. The patient cohort comprised 68 male and 20 female patients. Adenocarcinoma histology was identified in the majority of patients (56.8%). Nivolumab was administered to 74% of patients as a second line of treatment and to 26% in the third line or later. In ROC analysis, the ideal cutoff value for PIV was established at 652 (AUC: 0.691, 95% CI: 0.568-0.814, P = .013). No statistically significant differences were observed in the demographic and clinicopathological features of patients between the low- and high-PIV groups. High PIV was independently associated with shorter progressionfree survival (HR: 0.47, 95% CI: 0.29-0.76; P = .002) and overall survival (HR: 0.54, 95% CI: 0.32-0.92; P = .023), independent of other factors affecting outcomes. Conclusion: The findings of the study indicate that PIV value may serve as a significant prognostic biomarker for predicting survival in metastatic NSCLC patients undergoing treatment with nivolumab. Cite this article as: Guliyev M, Alan Ö, Fidan MC, et al. Evaluating the prognostic role of pan-immune-inflammation value in patients with advanced non-small cell lung cancer treated with nivolumab. Cerrahpaşa Med J. 2025, 49, 0038, doi:10.5152/ cjm.2025.25038.